Characterization of the mitochondrial unfolded protein response in human coronary artery endothelial cells. (3rd October 2022) - Al Zaidi, M; Repges, E; Jansen, F; Tiyerili, V; Zimmer, S; Nickenig, G; Aksoy, A
Abstract: Background: The unfolded protein response of the endoplasmic reticulum (UPRER) is highly activated in cardiovascular diseases and aims to restore homeostasis by improving protein folding. An analogue cytoprotective mitochondrial unfolded protein response (UPRMito) regulated by an orthologue of the activating transcription factor 5 (ATF5) was described in model organism c. elegans. However, in humans it is not clear if there is a distinct UPRMito, and if there is an activation of an UPRMito during stress induced by cardiovascular diseases. The endothelium is subjected to high levels of mitochondrial stress, e.g. in atherosclerosis. Purpose: To provide a systematic characterization of the UPRMito in human coronary artery endothelial cells (HCAEC). Methods and results: HCAEC were treated with Nicotinamide Riboside (NR), a NAD+ precursor that activates UPRMito without inducing cellular stress. NR treatment did not induce toxicity and improved cell viability at a concentration of 100μM NR. Quantitative PCR confirmed a dose-dependent upregulation of UPRMito markers. Additionally, we measured expression of ATF4, which is discussed to regulate an integrated stress response in mammals by activating both the UPRMito and UPRER. ATF4 upregulation upon NR treatment was more pronounced than ATF5 upregulation. Analysis of GTEX-Data showed that ATF5 is almost exclusively expressed in liver tissue, while ATF4 shows ubiquitous expression. Among 54 tissues, aortic tissue and coronary arterial tissue are among the five tissues with the highest ATF4 expression. Analysis of RNA-seq-data of human carotid atherosclerosis revealed that the two transcription factors are differentially regulated. ATF4 is downregulated in unstable plaque, while ATF5 is upregulated. Moreover, ATF4 is in both conditions highly more abundant than ATF5. Accordingly, endothelial cells incubated under atherosclerotic conditions (oxLDL + high glucose) exhibited a ATF4 down- and ATF5 upregulation. Genes previously described to be involved in the UPRMito exhibited a similar expression pattern as ATF4. To further elucidate these findings, we will perform transcriptomic analyses of HCAEC treated with atherosclerotic stimuli (IL-1β, oxLDL), UPRER inductors (Thapsigargin, Tunicamycin) and stressors of mitochondrial proteostasis (Oligomycin, MitoBloCK-6), to analyze, if ATF5- or ATF4-related pathways are dysregulated. Specific inhibitors and UPRMito activators will be used to investigate the significance of ATF4 and ATF5 on endothelial cell function (proliferation, migration, apoptosis, monocyte adhesion). Conclusion: The UPRMito is dysregulated during the pathogenesis of atherosclerosis in HCAEC. Further findings are required to elucidate, if the UPRMito is activated separately and specifically by ATF5 or as part of an integrated cellular stress response by ATF4. A deeper understanding of these stress responses is crucial for the identification of novel therapeutic targets in atherosclerosis. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): University hospital Bonn